Development of a Small-Scale Plastic Recycling Technology and a Special Filament Product for 3D Printing - Oussai , Alaeddine; Bártfai, Zoltán; Kátai, László; Szalkai, István (International Journal of Engineering and Management Sciences, 2019)
In our days, the fight against pollution has become a real challenge for the state. recycling is one of the solutions that is adopted in several nations to reduce the rate of plastic discarded in nature. The amount of plastic waste has been increasing for decades contributing to the environmental pollution that is one of the most serious problem of the mankind. according to the statistics not only the household plastic waste, but the industry discharge is increasing because the utilization of plastic as a raw material is more and more extending. plastic can be found in a lot of products, huge number of bottles, plastic bags, computers, auto parts are sold every day. The current applications for using recycled plastics in fabrication and design are fairly limited, on a small scale, plastics (such as abs, HDPe1, or Pe2t) are shredded and formed into pellets, and then either extruded into lament to be used in existing 3d printers, or injection molded into small parts and pieces of larger components. at a large scale, recycled HDpE is melted into sheets and either used directly as sheets in construction, or then heat formed from a sheet into components for construction. these methods of fabrication using recycled plastics are the norm because of their straightforward processes. nevertheless, each method leaves some complexity to be desired. This paper we study the types of plastics and diagnose the pollution caused by the latter. this allowed us to design and size a recycling station of plastic into filaments for three-dimensional printers. this station which will contribute to the fight against pollution. the station consists of two machines for grinding of the plastic and the other for the extrusion of the desired filaments. we were able to make a theoretical academic study on both machines and also we designed with solidworks 2015. The theoretical study is spread of the mechanical calculations necessary to the design and validation of the structure using the tools. as the prospect of this project, we want to complete the achievement of this station while completing the crusher and extruder mechanically. then switch to electric and electronic parts (introduction of engines, sensors and wiring...). In the case of waste plastics that are recyclable and reusable. the most widely used are polyethylene terephthalate (pet, used for synthetic fibers and water bottles), and second high-density polyethylene (hdpe, used for jugs, bottle caps, water pipes).